1984
DOI: 10.3102/10769986009004295
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Rate of Return to Interrupted Schooling

Abstract: The most widely followed technique to estimate the rate of return to a year of schooling was provided by Mincer (1974) . This paper extends Mincer's semilog wage regression method to include those who interrupted their schooling with years of work. Schooling and the duration of the interruption interact to create nonlinearities in the rate of return to schooling. The proposed method is then applied to both Vietnam era G.I. students and civilian interrupters. It is found that interrupters earn substantially the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The adjusted model with the lowest RSS is the one with the better fit. We conclude that the linear and logarithmic models are significantly different in terms of goodness of fit, and that the logarithmic specification for real wage rates is preferred 38 .…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The adjusted model with the lowest RSS is the one with the better fit. We conclude that the linear and logarithmic models are significantly different in terms of goodness of fit, and that the logarithmic specification for real wage rates is preferred 38 .…”
mentioning
confidence: 84%
“…Griliches' population of interest only includes men. Similarly, Marcus (1984) employs the same data that Griliches (1980) uses and shows that there is no substantial difference in the rate of return to education between interrupters and non-interrupters at the same level of schooling. Contrary to our analysis that controls for different reasons of discontinuous schooling, Marcus's study only focuses on those who interrupted their schooling with years of work.…”
Section: Survey Of Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies are mixed on whether older students receive a smaller return on their educational investment than those who complete their degrees earlier in life (Leigh and Gill 1997;Light 1995;Marcus 1984;Griliches 1980). Again, more research is needed that compares returns at different ages, different degree levels (for example, associate's versus bachelor's degrees), different types of institutions, and in different fields of study.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2015) also employ HILDA data in their study of underemployment and labour market trajectories of mature age Australian workers. 5 Griliches (1980), Marcus (1984), Light (1995) and Leigh and Gill (1997) study the effect of delaying entry to university using US panel surveys of young adults. The first two studies found that delayed entry did not adversely affect returns to education.…”
Section: Introductionmentioning
confidence: 99%